Post-Operative Resumption of Clear Liquids Orally at 2 Hours And 6 Hours, In Patients Undergoing Elective Surgeries Under General Anesthesia: A Comparative Study - Regmi, Nabin Kumar; Sharma, Anshu; Kharel, Subina (Journal of Nepalgunj Medical College, 2025)
Introduction: Early oral nutrition initiation is an essential component of multimodal perioperative care. It is associated with early intestinal function recovery, better immunity, improved wound healing, early ambulation, and decreased morbidity. However, a gap exists between postoperative feeding evidence and its practical application.Aims: To compare patient’s satisfaction regarding thirst and the occurrence of post-operative nausea, vomiting, and aspiration of gastric contents after resumption of clear liquid orally at 2 hours and 6 hours postoperatively.Methods: Ninety-six patients, aged 18 to 70 years, of either sex and ASA I to II, who underwent elective surgeries under general anesthesia, were randomly divided into two equal groups: group 1 and group 2. Patients in group 1 were given clear liquid orally at 2 hours, and group 2 at 6 hours postoperatively. Patient satisfaction regarding thirst, occurrence of postoperative nausea, vomiting, aspiration of gastric contents, and flatus time were compared between the two groups. SPSS 20 was used for data analysis. Student Ttest, Chi-square test, Fisher’s test, and Man-Whitney test were applied.Results: Gender distribution and mean age in both groups had no statistical difference, with P values of 0.358 and 0.331, respectively. The thirst distress scale and post-operative flatus time were significantly lower, whereas Likert’s satisfaction level regarding thirst was higher in group 1 compared to group 2, with P-values of 0.00, 0.038, and 0.001, respectively. APFEL grading and postoperative nausea and vomiting grading were statistically similar, with p-values of 0.26 and 0.116, respectively. No aspiration occurred in both groups.Conclusion: Compared to 6 hours, resumption of clear liquid 2 hours postoperatively after general anesthesia decreases thirst distress and post-operative flatus time, with the additional benefit of increasing patient satisfaction levels, without any difference in post-operative aspiration rate.